A Multi-Objective Optimization Approach for Fault-Tolerance Provisioning in Multi-Radio Hybrid Wireless-Optical Broadband Access Networks - Schutz, G. (2013)
Wireless-optical broadband-access networks (WOBANs), currently being deployed at the access section, should integrate fault-tolerance in their design so that geographically continuous wireless coverage can be provided without service breaks. In this paper we propose a joint wireless and optical fault-tolerance planning approach for WOBANs having multiple radios in each router. The problem is formalized, as a multi-objective optimization problem, and a heuristic is proposed to solve this problem. Two fault-tolerance planning scenarios, where gateways are arranged differently in the risk groups, are analysed. It is shown that multi-radio routers can be exploited to improve the performance of WOBANs, providing wireless and optical fault-tolerance. Results also indicate that, when using our approach, a small increase in the number of radios can significantly decrease the total capacity required to provide any degree of fault-tolerance.